(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The present study aimed to detect the degree of exercise The Arabic language teachers for creative thinking skills in the Directorate of Education for the North Eastern Badia region. The study’s sample consisted of (200) The Arabic language teachers for sixth and seven grades. To achieve the objectives of the study, the researcher used a questionnaire composed of (63) items. The results of the study showed that the degree of exercise The Arabic language teachers for creative thinking skills development of the student was moderate on the instrument total score, and in the fields of freedom of expression, the positive perspective towards creativity, teaching methods, methods of evaluation, the class environment, and creativity stimulation. Results of the study also pointed to the lack of a statistically significant degree in exercise The Arabic language teachers in the Directorate of Education for the North Eastern Badia region for creative thinking skills development differences depending on the variable: gender, experience, and qualifications of all fields of study. Accordingly, the study concluded that a number of recommendations related.